Restricted Epitope Specificity of Anti-FVIII Antibodies that Appeared during a Recent Outbreak of Inhibitors - Gilles, Jean Guy G; Peerlinck, Kathelijne; Arnout, Jef; Vermylen, Jos; Saint-Remy, Jean-Marie R (Thrombosis and Haemostasis, 1997)
We recently described an outbreak of anti-factor VIII (FVIII) antibodies in a population of haemophilia A patients non-responsive to FVIII (1). To find out what part of the FVIII molecule had been altered, we purified specific anti-FVIII antibodies from the plasma of the five patients showing high titres of inhibitors. An average of 100 µg antibodies per ml of initial plasma was recovered by immunoadsorption on insolubilised FVIII. The antibodies followed the normal isotypic distribution, including the presence of specific IgG2 antibodies; the relative increase in IgG4 that is usually observed in patients with long-standing inhibitors, was not present. The regions of FVIII to which human antibodies bound were determined by a competition assay using a panel of murine monoclonal antibodies: two major regions were identified, one located in the A2 heavy chain domain, and the other made of determinants of both the A3 and C2 light chain domains. Affinity-purified antibodies inhibited the function of FVIII as determined in a chromo- genic assay. However, variations existed in the affinities with which antibodies bound to soluble FVIII. This study shows that the immu- nogenicity of two particular regions of FVIII has been altered. A screening for alterations located in these two regions should possibly be included in the preclinical evaluation of FVIII concentrates.